Studies in natural products chemistry : Vol. 41 - Rahman, Atta-ur-, 1942- (Amsterdam : Elsevier, 2014)
Natural products in the plant and animal kingdom offer a huge diversity of chemical structures that are the result of biosynthetic processes that have been modulated over the millennia through genetic effects. With the rapid developments in spectroscopic techniques and accompanying advances in high-throughput screening techniques, it has become possible to isolate and then determine the structures and biological activity of natural products rapidly, thus opening up exciting new opportunities in the field of new drug development to the pharmaceutical industry. The series also covers the synthesis or testing and recording of the medicinal properties of natural products, providing cutting edge accounts of the fascinating developments in the isolation, structure elucidation, synthesis, biosynthesis and pharmacology of a diverse array of natural products. Describes the chemistry of bioactive natural products Contains contributions by leading authorities in the field. Presents exciting sources of new pharmacophores.
1. Recent insights into the emerging role of triterpenoids in cancer therapy : part II / Rosa Tundis, Francesco Menichini, and Monica Rosa Loizzo -- 2. Highlights of pentacyclic triterpenoids in the cancer settings / Jorge A.R. Salvador [and six others] -- 3. Immunomodulatory and anticancer activity of sea cucumber triterpene glycosides / Dmitry L. Aminin [and five others] -- 4. Bioactive annonaceous acetogenins / Robert E. Smith, Kevin Tran, and Kristy M. Richards -- 5. Bioactive naphthoquinones from higher plants / Ingrid Hook, Clive Mills, and Helen Sheridan -- 6. Antiobesity effects of natural products from an epigenetic perspective / Esther C.Y. Woon and Joel D.W. Toh -- 7. Natural polyphenols as potent inhibitors of DNA methyltransferases / Hamid Marzag [and four others] -- 8. The chemistry and bioactivity of Eucommia ulmoides oliver leaves / Tetsuya Hirata [and three others] -- 9. Aloe vera gel in food, health products, and cosmetics industry / Shabnam Javed and Atta-ur-Rahman -- 10. Synthesis of marine-derived carbasugar pericosines / Yoshihide Usami -- 11. Bioactive components from leaf vegetable products / Francisco J. Barba, Maria J. Esteve, and Ana Frigola -- 12. Milk fat globule membrane material : isolation techniques, health-beneficial properties, and potential applications / Thien Trung Le, John Van Camp, and Koen Dewettinck -- 13. Determination of the absolute configuration of natural product molecules using vibrational circular dichroism / Joao M. Batista and Vanderlan da Silva Bolzani -- 14. Bioactive metabolites from rare actinomycetes / Kavita Tiwari and Rajinder K. Gupta.
Includes bibliographical references.
Print version record.
Keywords: Bioorganic chemistry; Bioactive compounds; Natural products; SCIENCE -- Life Sciences -- Biochemistry; Bioactive compounds; Bioorganic chemistry; Natural products; Electronic books